Análisis de la interacción entre el empleo, la inflación y las exportaciones y sus efectos en el crecimiento económico de Colombia durante el periodo 2005-2019 (2024)
Colombia has faced various challenges for its development, which is why growth will be addressed initially and subsequent to the factors that influence during the period of economic behavior. The choice to consider the period from 2005 to 2019 to identify the determining factors in Colombia's economic growth is relevant, given that it is currently a period of current interest. Facilitating an analysis of the policies and economic changes that have taken place in a specific context, providing highly useful information for decision-making in the present and future. Furthermore, by studying Colombian socioeconomic history, it will allow us to make a comparison with other periods and situations, which gives us the possibility of enriching the understanding of economic trends and challenges for the country.